The Effect of Employee Proficiency and Equipment Readiness on Oil Spill Response at Special Terminal PT Orbit Terminal Merak in 2020 - M, Dwi Priyanto; Lasse, D.A; Pahala, Yosi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
PT OTM is a company engaged in the field of independent bulk terminal and storage services for petroleum products in Indonesia, and functions as a distribution terminal. Currently, the products stored and distributed by PT OTM are Pertamax, Pertalite and Premium. The purpose of this study was to determine and analyze the effect of employee skills and equipment readiness on oil spill management at Special Terminal PT Orbit Terminal Merak in 2020. The study was conducted in the territorial waters of the Malacca Strait using quantitative methods, with the number of research samples taken based on the Slovin formula of 47 people. Data were collected through instruments in the form of statement sheets with a Likert scale model that had been tested. The study used path analysis techniques. The results showed that the influence of employee skills on equipment readiness at Special Terminal PT Orbit Terminal Merak was 80.7%. Based on the hypothesis test Significance t = 0.000 <0.05 so that the influence is significant; The influence of employee skills on oil spill management at Special Terminal PT Orbit Terminal Merak is 43.1%. Based on the hypothesis test Significance t = 0.005 <0.05 so that the influence is significant; The magnitude of the influence of equipment readiness on oil spill management at Special Terminal PT. Orbit Terminal Merak is 43.6%. Based on the hypothesis test Significance t = 0.004 <0.05 so that the influence is significant; There is an influence of employee skills on oil spill management with equipment readiness as a mediating variable at Special Terminal PT. Orbit Terminal Merak. The p-value of 0.000 is smaller than the real level or 0.000 <0.05 so that equipment readiness can be a mediator of employee skills on oil spill management.